Web-Based Leave Application Information System (Sipecut) With Rapid Application Development Method - Andi Taufik; Fattya Ariani (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
One of the factors in the company's business continuity is human resources. To make human resources good and responsible, the company must be able to give rights to its employees, not just the obligations required in the job. One of their rights is leave. Currently, many companies use a manual system for submitting leave by submitting a letter or leave form first to the HRD department and waiting a long time to find out the results of the submission. The manual system has several problems, such as missing and damaged files, it takes a long time because it has not been integrated into a computerized system, it is not effective in its work process, because of the large amount of paper usage and it is difficult to control submissions. Therefore, a leave application information system (SIPECUT) was created to overcome this. This system is made web-based using the Rapid Application Development (RAD) method. With this system, it is easier for employees to process the application and circulation of leave approval. Data is stored properly so that no data is lost. Reporting to the leadership is even easier